Análise de material didático com base em tipos e gêneros textuais - Vasques, Renata dos Reis (2013)
This paper aims at analyzing one collection of materials in Portuguese Language, more utilization in the third and fourth cycles of the new school, shown in the National Book Program PNLD (2011-2013), considering the methodology used by the authors in relation to text production and reading, based on types and genre. To justify theoretically this research, we selected the works of João Wanderley Geraldi, Mikhail Bakhtin, Luiz Antônio Marcuschi e Patrick Charaudeau